1998
DOI: 10.1002/(sici)1099-0739(199802)12:2<99::aid-aoc674>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phenyltin compounds on lipid bilayer organization

Abstract: Phenyltin compounds are known to be biologically active. Their chemical structure suggests that they are likely to interact with the lipid fraction of cell membranes. Using fluorescence and NMR techniques, the effect of phenyltin compounds on selected regions of model lipid bilayers formed from phosphatidylcholine was studied. The polarization of N‐(7‐nitrobenz‐2‐oxa‐1,3‐diazol‐4‐yl) dipalmitoyl‐L‐phosphatidylethanolamine and desorption of praseodymium ions was used to probe the polar region, whereas the polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Consequently, both compounds are located in different membrane re gions and affect the lipid bilayer differently. The surface charge introduced onto the membrane sur face by triphenyltin was bigger but disturbance within the hydrophobic core was more eminent when diphenyltin was present (Langner et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, both compounds are located in different membrane re gions and affect the lipid bilayer differently. The surface charge introduced onto the membrane sur face by triphenyltin was bigger but disturbance within the hydrophobic core was more eminent when diphenyltin was present (Langner et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…The ESI-MS (Table 3) and MS/MS data suggested that the additional peak at m/z 764.1 in a mass spectrum of their mixture was derived from TPT and FePCH, demonstrating the existence of the TPT-FePCH complex. A change of signal splitting in 1 H NMR spectrum can be used as a measure of the degree of complex formation (15). In 1 H NMR spectrum (Fig.…”
Section: Discussionmentioning
confidence: 99%